Respuesta :

4(a) . a^2 + b^2 = c^2....where a and b are the legs and c is the hypotenuse
          12^2 + b^2 = 13^2
          b^2 = 13^2 - 12^2
          b^2 = 169 - 144
          b^2 = 25
          b = sqrt 25
          b = 5 <== ur missing leg(t) = 5

  (b)   a^2 + b^2 = c^2
          a^2 + 9^2 = 12^2
          a^2 = 12^2 - 9^2
          a^2 = 144 - 81
          a^2 = 63
          a = sqrt 63
          a = 7.9 <== ur missing leg(a)

(c) a^2 + b^2 = c^2
     6^2 + 9^2 = c^2
      36 + 81 = c^2
      117 = c^2
       sqrt 117 = c
       10.8 = c <== ur hypotenuse (x)